The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.17221/15/2015-pse
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of management practices on gas emissions and N losses calculated with denitrification-decomposition model

Abstract: The study presents the impact of management practices on greenhouse gas emissions (GHG) and nitrogen (N) losses calculated with a denitrification-decomposition model. Two cropping systems were analysed. The first rotation (A) consisted of potato, winter wheat, spring barley and corn. The second (B) included potato, winter wheat, spring barley and clover with grasses mixture. In A1 and B1 scenarios, fluxes were estimated on the basis of mineral fertilizers input, whereas in A2 and B2 scenarios the assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Our study showed that tillage treatments affect soil CO2 emissions, which agrees with several other studies [15,39], where CO2 release varied with agricultural practices. Figure 3 presents two-year average soil C-CO2 emissions (n = 48) considering tillage treatments.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 93%
“…Our study showed that tillage treatments affect soil CO2 emissions, which agrees with several other studies [15,39], where CO2 release varied with agricultural practices. Figure 3 presents two-year average soil C-CO2 emissions (n = 48) considering tillage treatments.…”
Section: Influence Of Tillage Treatment On Soil C-co2 Emissionssupporting
confidence: 93%
“…When formulating an action plan, it is necessary to pay particular attention to exploring the potential of agricultural and rural areas (including agricultural soils) in order to reduce GHG emissions. For example, Syp et al (2015), when assessing the impact of management practices on gas emissions and N losses calculated using the DNDC model, state that the N losses and GHG emissions could be minimized by controlling N application through the implementation of a nutrient management plan in which N doses are defined based on the crop needs and soil quality. However, as emphasized by Bennetzen et al (2016), agricultural GHG emissions can only be reduced to a certain level and a simultaneous focus on other parts of the food-system is necessary in order to increase food security whilst reducing emissions.…”
Section: Resultsmentioning
confidence: 99%